Electrostatic Actuating Double‐Unit Electrocaloric Cooling Device with High Efficiency. Issue 13 (12th February 2021) - Bo, Yiwen; Zhang, Quan; Cui, Heng; Wang, Mengyan; Zhang, Chunyang; He, Wen; Fan, Xiangqian; Lv, Yiwen; Fu, Xiang; Liang, Jiajie; Huang, Yi; Ma, Rujun; et al.
Abstract: Compact solid‐state refrigeration systems that offer a high specific cooling power and a high coefficient of performance (COP) are desirable in a wide range of applications where efficient and localized heat transfer is required. Here, a double‐unit electrocaloric (EC) polymer‐based refrigeration device with high intrinsic thermodynamic efficiency is demonstrated using a flexible EC polymer film with improved performance by doping plasticizer and an electrostatic actuation mechanism. The double‐unit refrigeration device achieves a large temperature span of 4.8 K, which is 71% higher than that of the single‐unit device. A specific cooling power of 3.6 W g −1 and a maximum COP of 8.3 for the cooling device are produced. The surface temperature of a central processing unit (CPU) cooled by an active EC device is 22.4 K lower than that of the CPU cooled in air. The highly efficient and compact EC cooling device demonstrated here not only leapfrogs the performance of existing solid‐state cooling technologies, but also brings solid state cooling closer to reality for a variety of practical applications that require compact or mechanically flexible refrigeration. Abstract : Electrocaloric cooling technology provides an effective alternative cooling plan for thermal regulation of microelectronics. Plasticizer modification effectively improves intrinsic electrocaloric performance of electrocaloric polymers. The modified electrocaloric polymer‐based refrigeration device with a maximum temperature span of 4.8 K has a high cooling efficiency. There is a 21.7 K temperature drop in a running central processing unit cooled by the electrocaloric refrigeration device.